The high energy Universe at ultra-high resolution: the power and promise of X-ray interferometry - Uttley, Phil; Hartog, Roland Den; Bambi, Cosimo; Barret, Didier; Bianchi, Stefano; Bursa, Michal; Cappi, Massimo; Casella, Piergiorgio; Cash, Webster; Costantini, Elisa; Dauser, Thomas; Trigo, Maria Diaz; et al. (Experimental Astronomy, 2021)
We propose the development of X-ray interferometry (XRI), to reveal the Universe at high energies with ultra-high spatial resolution. With baselines which can be accommodated on a single spacecraft, XRI can reach 100 μ as resolution at 10 Å (1.2 keV) and 20 μ as at 2 Å (6 keV), enabling imaging and imaging-spectroscopy of (for example) X-ray coronae of nearby accreting supermassive black holes (SMBH) and the SMBH ‘shadow’; SMBH accretion flows and outflows; X-ray binary winds and orbits; stellar coronae within ∼ 100 pc and many exoplanets which transit across them. For sufficiently luminous sources XRI will resolve sub-pc scales across the entire observable Universe, revealing accreting binary SMBHs and enabling trigonometric measurements of the Hubble constant with X-ray light echoes from quasars or explosive transients. A multi-spacecraft ‘constellation’ interferometer would resolve well below 1 μ as, enabling SMBH event horizons to be resolved in many active galaxies and the detailed study of the effects of strong field gravity on the dynamics and emission from accreting gas close to the black hole.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Instrumentation; Interferometry; X-ray astronomy